Mesenchymal Stem Cell-Derived Exosomes in Skin Wound Healing and Scar Prevention: Mechanisms, Comparison, and Clinical Prospects - Yaoyao Song; Fei Xie; Xiangdang Liang (Tissue Engineering and Regenerative Medicine, 2026)
Background: Exosomes derived from mesenchymal stem cells (MSCs) have garnered significant research interest for their roles in promoting wound healing and preventing scar formation. Studies have shown that MSC-derived exosomes (MSC-Exos) accelerate the repair of cutaneous and corneal wounds through multiple mechanisms, including modulation of cell migration, anti-inflammatory responses, inhibition of apoptosis, collagen remodeling, and promotion of angiogenesis. Notably, exosomal miRNAs play a pivotal role in inhibiting fibroblast-to-myofibroblast transformation and modulating the TGF-β signaling pathway, thereby effectively reducing scar formation. Promising outcomes of exosomes derived from adipose tissue- and umbilical cord blood-derived MSCs in various wound models underscore their clinical potential. Methods: This review systematically elaborates on the specific mechanisms by which MSC-Exos promote wound healing and inhibit scar formation, and summarizes their application outcomes in different wound models. Additionally, it explores current advanced biomaterial delivery systems designed to optimize exosome delivery, aiming to provide insights and future directions for the clinical translation of MSC-Exos. Results and conclusion: MSC-Exos effectively promote tissue repair and reduce scarring through multi-target and multi-pathway mechanisms, demonstrating significant clinical application prospects. Delivery systems incorporating biomaterials hold promise for further enhancing their therapeutic efficacy and stability. Future research should focus on elucidating the molecular mechanisms of exosome action, developing scalable preparation protocols, and conducting preclinical and clinical evaluations to advance their translation into clinical therapeutic applications.